THE IMPLEMENTATION OF COOPERATIVE LEARNING BY USING A JIGSAW TECHNIQUE IN SPEAKING TO THE GRADE XI STUDENTS OF SMK NEGERI 9 MEDAN - Bakara, Julita; Pasaribu, Arsen Nahum (Unversitas Katolik Santo Thomas, 2022)
This study was investigating the Implementation of the Jigsaw technique in speaking To the Grade XI Students of SMKN 9 Medan. This study used an experimental design. The instruments for collecting data were tests and questionnaires. The population in this study were all the grade XI students of SMKN 9 Medan and two classes were taken as samples, each class consisting of 30 students. One class was an experimental group (30 students of grade XI-RPL2) and one class was as a control group (30 students of grade XI-TKJ3). The experimental group was taught by jigsaw strategy while the control group which consisted of 30 students was taught by using a conventional method. The finding of this study shows that the Jigsaw technique used in teaching speaking affected the students' speaking scores. The mean score of pre-test and post-test for the control class were 65,53 and 75,77 which shows only a slight difference of 10,24 points. While the mean score in the pre-test and post-test of the experimental class was 69,81 and 81,30 with a difference of 11,49 points. Although it shows a slight difference between the two means, the result shows that the post-test of the experimental class was better than Post-test in the control class. It can be concluded that the students who were taught through the Jigsaw technique achieved a better performance in speaking than those who were not taught through the Jigsaw technique. In addition, the result of the questionnaires shows that the students became more active and productive by discussing ideas since the interactive classroom atmosphere and joyful learning helped them to be more confident to express ideas orally. Keywords: Cooperative Learning, Jigsaw Technique, Speaking